Low-Complexity Oversampled OTFS Receivers With Reduced Overhead - Narendra Deconda; Srikrishna Bhashyam; Nambi Seshadri; R. David Koilpillai (IEEE Open Journal of the Communications Society)
Orthogonal Time Frequency Space (OTFS) modulation enables reliable communication in fast time-varying, frequency-selective channels. It is a delay-Doppler (DD) domain modulation that models the information symbols and the channel in the DD domain. This paper considers a pulse-shaped OTFS system with oversampling at the receiver. To mitigate Inter-Frame and Inter-Block Interference, we propose a Reduced Cyclic Prefix (RCP) and Reduced Cyclic Suffix (RCS) frame structure for the OTFS systems that need significantly less overhead than the existing Zero-padded OTFS frame structure. At the receiver, we propose a Finite Impulse Response filter-based Noise Whitening and an iterative delay-time domain Maximal Ratio Combining equalizer that has low complexity and employs oversampling. Through Monte Carlo simulations, we show improved system error performance with oversampling and excess bandwidth. The proposed equalizer provides a significant complexity reduction compared to the existing Message-passing equalizer for a minimal degradation in error performance. We then simulate a Matched Filter Bound (MFB) for OTFS systems. The proposed equalizer is within 3 dB of the MFB performance at an error rate of 10-4.